Extraction of Antioxidants from Borage (Borago officinalis L.) Leaves-Optimization by Response Surface Method and Application in Oil-in-Water Emulsions - Francisco Segovia; Bryshila Lupo; Sara Peiró; Michael H. Gordon; María Pilar Almajano (MDPI AG, 2014)
Borage (Borago officinalis L.) is a typical Spanish plant. During processing, 60% are leaves. The aim of this work is to model and optimize the extraction of polyphenol from borage leaves using the response surface method (RSM) and to use this extract for application in emulsions. The responses were: total polyphenol content (TPC), antioxidant capacity by ORAC, and rosmarinic acid by HPLC. The ranges of the variables temperature, ethanol content and time were 50-90 °C, 0%-30%-60% ethanol (v/v), and 10-15 min. For ethanolic extraction, optimal conditions were at 75.9 °C, 52% ethanol and 14.8 min, yielding activity of 27.05 mg GAE/g DW TPC; 115.96 mg TE/g DW in ORAC and 11.02 mg/L rosmarinic acid. For water extraction, optimal activity was achieved with extraction at 98.3 °C and 22 min, with responses of 22.3 mg GAE/g DW TPC; 81.6 mg TE/g DW in ORAC and 3.9 mg/L rosmarinic acid. The significant variables were ethanol concentration and temperature. For emulsions, the peroxide value was inhibited by 60% for 3% extract concentration; and 80% with 3% extract concentration and 0.2% of BSA. The p-anisidine value between the control and the emulsion with 3% extract was reduced to 73.6% and with BSA 86.3%, and others concentrations had similar behavior.